Noise-Induced Hearing Loss Among Greek Solid Waste Landfill Workers - Papastergiou, St.; Karaiskos, C.; Damikouka, I.,; Douna, E.,; Koupidis, S.; Dounias, G. (European Scientific Journal, ESJ, 2025)
Introduction: Hearing loss at work is currently considered the most common cause of permanent hearing loss in adults and one of the most important health problems with economic and psychosocial consequences. The present study has the aim to investigate the prevalence and the determinants of hearing loss among solid waste workers. Material and methods: Eight-three (83) solid waste workers underwent audiometric test in the facilities of the Integrated Solid Waste Management Facility (OEDA) in the area of Αttica, Greece. To assess hearing, an occupational history was first taken, followed by an otoscopy and audiogram. The findings of the audiograms were initially assessed as normal and pathological and then classified using diagnostic criteria (NIOSH, OYDOS). Findings: Statistical analysis has shown that 23% of solid waste workers had sensorineural hearing loss located mainly at 4000 Hz. Multivariate analysis confirmed that the intensity of occupational exposure to noise appears to be the strongest predictor of noise-induced hearing loss (p=0.02326) followed by the years of work (p=0.02728). Particularly, the analysis with the NIOSH criterion (probability of having a positive NIOSH criterion in at least 1 of both ears) increased by 1.33 times/year or 32.84%/year on average. Finally, no univariate statistically significant associations were found with any of the two criteria and smoking, BMI, hypertension or tinnitus Estimating exposure through self-reported data is not sufficient and accurate and in fact workers who are exposed to higher risk measures tend to underestimate the risk. Conclusion: Our findings indicate that solid waste workers are occupationally exposed to high levels of noise, and present high rates of noise-induced hearing loss (NIHL). It is necessary to estimate the noise exposure with appropriate measurements in the work environment (individual sound exposure of employees and environmental measurements in the workplace) and take appropriate measures.